Gibberellin Metabolism in Flowering Plants: An Update and Perspectives - He, Juan; Xin, Peiyong; Ma, Xueting; Chu, Jinfang; Wang, Guodong (Frontiers in Plant Science, 2020)
In plants, gibberellins (GAs) play important roles in regulating growth and development. Early studies revealed the large chemodiversity of gibberellins in plants, but only GA1, GA3, GA4, and GA7 show biological activity that controls plant development. However, the elucidation of the GA metabolic network at the molecular level has lagged far behind the chemical discovery of GAs. Recent advances in downstream GA biosynthesis (after GA12 formation) suggest that species-specific gibberellin modifications were acquired during flowering plant evolution. Here, we summarize the current knowledge of GA metabolism in flowering plants and the physiological functions of GA deactivation, with a focus on GA 13 hydroxylation. The potential applications of GA synthetic biology for plant development are also discussed.